Analisis Tindak Tutur Lokusi Dalam Video Pembelajaran Bahasa Indonesia Pada Kanal Youtube Bimbel Smart - Natasya Kusumaningtyas; Aulia Umi Pertiwi; Khusni Zihrotun Umniyah; Khoirin Nada Lutfiyatul Muna; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Ryan Hidayat (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
One thing that will always be present in a communication process is speech acts. As something that is always present in the communication process, speech acts will always involve speakers, listeners, and what will be discussed. Speech acts are linguistic studies that aim to convey the intent and purpose of the speaker to the speech partner. This study will examine the speech acts contained in Indonesian language learning videos. The speech acts to be analyzed are focused on locutionary speech acts. The data source used is Indonesian learning videos on the BimBel Smart YouTube channel. The data used is in the form of utterances in the video which are included in the type of locutionary speech act. The type of research used in this research is qualitative research with pragmatic methods with data collection techniques in the form of listening and note-taking techniques. The data found were 31 locutionary speech acts in 5 different Indonesian language learning videos contained on the BimBel Smart YouTube channel. By conducting this analysis, it is hoped that readers can obtain information about locutionary speech acts in Indonesian language learning videos, especially those contained on the BimBel Smart YouTube channel.